2005
DOI: 10.1128/aem.71.7.3978-3986.2005
|View full text |Cite
|
Sign up to set email alerts
|

Diel Variations in Carbon Metabolism by Green Nonsulfur-Like Bacteria in Alkaline Siliceous Hot Spring Microbial Mats from Yellowstone National Park

Abstract: Green nonsulfur-like bacteria (GNSLB) in hot spring microbial mats are thought to be mainly photoheterotrophic, using cyanobacterial metabolites as carbon sources. However, the stable carbon isotopic composition of typical Chloroflexus and Roseiflexus lipids suggests photoautotrophic metabolism of GNSLB. One possible explanation for this apparent discrepancy might be that GNSLB fix inorganic carbon only during certain times of the day. In order to study temporal variability in carbon metabolism by GNSLB 14 C]b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
104
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(115 citation statements)
references
References 52 publications
10
104
0
1
Order By: Relevance
“…This pathway, which is known to be used by Chloroflexus spp., results in isotopically heavier organic carbon than that fixed in the Calvin cycle (21,22,40,43). This photoautotrophic biochemistry of FAPs in the mat was confirmed in labeling experiments using 13 C-labeled bicarbonate, which suggested that the 13 C label was incorporated into FAP biomarkers and FAP biomass (46,47). However, Roseiflexus spp., not Chloroflexus spp., are the dominant mat FAPs, and R. castenholzii has not been shown to grow photoautotrophically (20).…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…This pathway, which is known to be used by Chloroflexus spp., results in isotopically heavier organic carbon than that fixed in the Calvin cycle (21,22,40,43). This photoautotrophic biochemistry of FAPs in the mat was confirmed in labeling experiments using 13 C-labeled bicarbonate, which suggested that the 13 C label was incorporated into FAP biomarkers and FAP biomass (46,47). However, Roseiflexus spp., not Chloroflexus spp., are the dominant mat FAPs, and R. castenholzii has not been shown to grow photoautotrophically (20).…”
mentioning
confidence: 78%
“…Although a recent pyrosequencing study argued against this producer-consumer relationship (33), we have observed evidence that 13 CO 2 fixed by Synechococcus spp. into polyglucose is transferred to FAPs via assimilation of [ 13 C]acetate derived from cyanobacterial fermentation (46). Compound-specific stable carbon isotope studies of FAP biomarkers also suggested that FAPs may be photoautotrophic (42,45).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of such phototrophs is, however, expected to be affected by the local oxygen concentration. For example, filamentous anoxygenic phototrophs (also known as green non-sulphur bacteria) can switch from sulphide-driven anoxygenic P to photoorganoheterotrophy or aerobic respiration when oxygen and cyanobacterial excudates are available in the light ( Van der Meer et al, 2005;Polerecky et al, 2007). Additionally, anaerobic anoxygenic phototrophs, such as green and purple sulphur bacteria, are expected to be poisoned by high oxygen concentrations (Van Gemerden and Mas, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Autotrophic CO 2 assimilation by the representatives of family Oscillochloridaceae is performed through the reductive pentose phosphate cycle (Berg et al, 2005;Ivanovsky et al, 1999;Turova et al, 2006). FAPs belonging to the family Roseiflexaceae are photo-organotrophs, and they do not grow photolithotrophically as pure cultures (Hanada et al, 2002), but it has been suggested that Roseiflexus is capable of growing photo-autotrophically in hot spring microbial mats (van der Meer et al, 2005(van der Meer et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%